Testosterone treatment is not associated with increased risk of adverse cardiovascular events: results from the Registry of Hypogonadism in Men (RHYME). Issue 10 (October 2016) - Maggi, Mario; Wu, Frederick C.W.; Jones, Thomas H.; Jackson, Graham; Behre, Hermann M.; Hackett, Geoffrey; Martin‐Morales, Antonio; Balercia, Giancarlo; Dobs, Adrian S.; Arver, Stefan T.E.; Maggio, Marcello; Cunningham, Glenn R.; et al.
Summary: Aims: The aim of this study was to assess cardiovascular (CV) safety of testosterone replacement therapy (TRT) in a large, diverse cohort of European men with hypogonadism (HG). Methods: The Registry of Hypogonadism in Men (RHYME) was designed as a multi‐national, longitudinal disease registry of men diagnosed with hypogonadism (HG) at 25 clinical sites in six European countries. Data collection included a complete medical history, physical examination, blood sampling and patient questionnaires at multiple study visits over 2–3 years. Independent adjudication was performed on all mortalities and CV outcomes. Results: Of 999 patients enrolled with clinically diagnosed HG, 750 (75%) initiated some form of TRT. Registry participants, including both treated and untreated patients, contributed 23 900 person‐months (99.6% of the targeted) follow‐up time. A total of 55 reported CV events occurred in 41 patients. Overall, five patients died of CV‐related causes (3 on TRT, 2 untreated) and none of the deaths were adjudicated as treatment‐related. The overall CV incidence rate was 1522 per 100 000 person‐years. CV event rates for men receiving TRT were not statistically different from untreated men ( P =.70). Regardless of treatment assignment, CV event rates were higher in older men and in those with increased CV risk factors or a prior history of CV events. Conclusions: Age and prior CV history, not TRT use, were predictors of new‐onset CV events in this multi‐national, prospective hypogonadism registry.